2021
DOI: 10.1007/s43630-021-00089-9
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic activity of silica and silica-silver nanocolloids based on photo-induced formation of reactive oxygen species

Abstract: Semiconductor nanomaterials are often proposed as photocatalysts for wastewater treatment; silica nanomaterials are still largely unexploited because their photocatalytic performances need improvements, especially under visible light. The present study is a proof-of-concept that amorphous silica colloids once submitted to the proper surface modifications change into an efficient photocatalyst even under low-energy illumination source. For this reason, silica-based colloidal nanomaterials, such as bare (SiO2 NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…After the cleaning process, the spectrum in Figure 4 e did not show any significant peaks related to MB and is very similar to the pristine SiC foam before use, indicating that the applied washing procedure efficiently regenerates the SiC foam and its photocatalytic properties are likely to be conserved. Interestingly, the signal coming from Si-O tends to decrease, which could reveal a reduction of surface silica species during the photocatalytic reaction as reactive oxygen species could be activated during the process [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…After the cleaning process, the spectrum in Figure 4 e did not show any significant peaks related to MB and is very similar to the pristine SiC foam before use, indicating that the applied washing procedure efficiently regenerates the SiC foam and its photocatalytic properties are likely to be conserved. Interestingly, the signal coming from Si-O tends to decrease, which could reveal a reduction of surface silica species during the photocatalytic reaction as reactive oxygen species could be activated during the process [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, surface-bound free radicals on crystalline silica particles can enhance oxidative stress via a surface reaction to generate ROS (Fubini and Hubbard, 2003). Besides, studies have shown that some particular metalbased NPs, such as TiO 2 NPs can generate ROS through a photocatalytic process under light irradiation (Toloman et al, 2019;Balaji et al, 2020;Romolini et al, 2021). Additionally, transition metals in NPs such as copper (Cu), and chromium (Cr) can participate in ROS generation via Fenton and Haber-Weiss reactions, ultimately enhancing oxidative stress (Huang et al, 2010;Angele-Martinez et al, 2017).…”
Section: Mechanisms Of Metal-based Nanoparticle Toxicitymentioning
confidence: 99%
“…In the early 70's scientist Fujishima and Honda first demonstrated TiO 2 as an outstanding photocatalyst to achieve solar-assisted water splitting reaction [6] and later, various investigations have been performed with different types of semiconductors. [7][8][9][10][11][12][13][14][15] Being an n-type semiconductor with TiO 2 has the ability and adequate potential to split the H 2 O molecule into H 2 and O 2 if a photon is absorbed during illumination when an interaction occurs with the electrolyte. [16,17] However, the performance of TiO 2 is relatively poor due to its wide band gap energy (~3.2 eV) and is not being suitable for all purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to easement of fabrication, better stability and appropriate electrical properties, all inorganic semiconductors are considered as promising materials for photo‐activated water splitting reaction. In the early 70’s scientist Fujishima and Honda first demonstrated TiO 2 as an outstanding photocatalyst to achieve solar‐assisted water splitting reaction [6] and later, various investigations have been performed with different types of semiconductors [7–15] . Being an n‐type semiconductor with TiO 2 has the ability and adequate potential to split the H 2 O molecule into H 2 and O 2 if a photon is absorbed during illumination when an interaction occurs with the electrolyte [16,17] .…”
Section: Introductionmentioning
confidence: 99%